HUBUNGAN TINGKAT PEMAKAIAN MEDIA SOSIAL TERHADAP SIMTOM DEPRESI PADA SISWA MADRASAH ALIYAH NEGERI 1 MEDAN - FERINI RATU SARAH HASIBUAN; DWI MAYAHETI NASUTION (JURNAL ILMIAH KOHESI, 2021)
Social networking sites in Indonesia are very popular and widely used, especially among teenagers and young adults. Basedon the survey results of the Indonesian Internet Service Providers Association (APJII) in 2017, around 87.13% of the numberof internet users use the internet to access social media. According to several studies saying that the use of socialnetworking sites has an adverse effect on personal, social, professional life, and is positively correlated with depressivesymptoms and negatively correlated with self-esteem. To find out the relationship between the level of use of social media ondepressive symptoms in Madrasah Aliyah Negeri 1 Medan students. This study was an observational analytic crosssectionaldesign and data was collected with an unbalanced categorical analytical formula. Low social media use withsymptoms of mild depression by 2 people (66.7%), Normal social media use with symptoms of mild depression by 0 people(0%), High social media use with symptoms of mild depression by 4 people (16.7%), symptoms of moderate depression asmany as 1 people (4.2%). Very high social media use with symptoms of mild depression as many as 21 people (42.9%),symptoms of moderate depression were 6 people (12.2%) and severe were 4 (8.2%). From the analysis data, P = 0.089 (P>0.05) shows that there is no correlation between the level of social media usage and depressive symptoms. The level of useof social media can not cause symptoms of depression.